Faktor Determinan Kesiapan Penerapan Standar Akuntansi Pemerintahan Berbasis Akrual di Manggarai, Nusa Tenggara Timur - Alfonsus Jantong (Matra Pembaruan: Jurnal Inovasi Kebijakan, 2017)
This study is to analyze the readiness of local government in applying accrual-based governmental accounting standard. The effect of training, mentoring on human resource and the effect of human resource’s quality, organizational commitment, and infrastructure on the readiness of the application of accrual-based governmental accounting standard are analyzed through positivist approach. The data is collected from 104 respondents through questionnaires distributed to SKPDs (local government agencies) working in accounting and to treasurers. The data is then analyzed using multiple regression method. The results show that training and mentoring positively affect the quality of human resource. The quality of human resource and infrastructure do not affect the readiness of accrualbased governmental accounting standard application. The quality of human resource, organizational commitment, and infrastructure simultaneously affect the readiness of accrual-based governmental accounting standard application. This research proves that local government of Manggarai, in terms of human resource and infrastructure, is not ready. The organizational commitment of Regency of Manggarai is ready to apply accrual-based governmental accounting standard.